The effects of ultraviolet radiation on the human immune system - DUTHIE, M. S; KIMBER, I; NORVAL, M (British journal of dermatology (1951), 1999)
The adverse outcome of increased ultraviolet (UV) irradiation on human health is currently of concern. While many experiments have been carried out in rodent models, fewer have been designed to test the effects of UV exposure in human subjects. This review concentrates on the modulations induced in the human immune system by UV, and outlines changes in antigen presentation by Langerhans cells and macrophages, in the activities of natural killer cells and T cells, and in cytokine regulation. Precautionary measures which might be taken to help protect people against the immunosuppressive action of UV irradiation are considered.